Strategi Pembelajaran Calistung di PAUD As-Safira yang Sesuai dengan Perkembangan Anak Usia Dini - Usman, Usman; Suryana, Cecep; Fahriyah, Elis; Nurzakiyah, Lia; Arianti, Vera Desi; Yoseptry, Ricky; Wasliman, Eva Dianawati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research aims to evaluate Calistung learning strategies (reading, writing and arithmetic) at As-Safira PAUD located in Cijedil Village, Cugenang District, Cianjur Regency, with a focus on the effectiveness of the methods used in improving the basic skills of early childhood. This research uses descriptive qualitative methods, involving observation, interviews and documentation as data collection techniques. It is hoped that the results of this research will provide insight into effective learning practices and recommendations for improving teaching strategies in the future.